A Compact UWB Antenna with a Quarter-Wavelength Strip in a Rectangular Slot for 5.5 GHz Band Notch - Pichet Moeikham; Chatree Mahatthanajatuphat; Prayoot Akkaraekthalin (International Journal of Antennas and Propagation)
The limitation of the electromagnetic interferences (EMIs) caused by UWB radiating sources into WLAN/WiMAX communication systems operating in the frequency band located around 5.5 GHz requires the adoption of appropriate design features. To this purpose, a notch filter integrated into an UWB antenna, which is able to ensure a better electrical insulation between the two mentioned communication systems with respect to that already presented by the authors Moeikham et al. (2011), is proposed in this paper. The proposed filter, consisting in a rectangular slot including a quarter-wavelength strip integrated on the lower inner edge of the UWB radiating patch, is capable of reducing the energy emission in the frequency range between 5.1 and 5.75 GHz resulting in lower EMIs with sensible electronic equipments working in this frequency band. The antenna structure has no need to be tuned after inserting the rectangle slot with a quarter-wavelength strip. The proposed antenna has potential to minimize the EMIs at a frequency range from 5.1 to 5.75 GHz. The radiation patterns are given nearly omnidirectional in plane and likely bidirectional in plane at all frequencies by the proposed antenna. Therefore, this antenna is suitable to apply for various UWB applications.